Alterations of the gut microbiome in Chinese patients with systemic lupus erythematosus. Issue 1 (December 2016) - He, Zhixing; Shao, Tiejuan; Li, Haichang; Xie, Zhijun; Wen, Chengping
Abstract Background Systemic lupus erythematosus (SLE) in patients from Spain is associated with intestinal dysbiosis. This study explores whether the alteration of the gut microbiome in SLE patients from China is consistent with the intestinal dysbiosis of SLE patients from Spain. Results The depletion of Firmicutes and the enrichment of Bacteroidetes in SLE patients from China were consistent with the SLE patients from Spain. Furthermore, we found that nine genera of gut microbiota were SLE-related microorganisms in Chinese subjects. GeneraRhodococcus, Eggerthella, Klebsiella, Prevotella, Eubacterium, Flavonifractor andIncertae sedis were significantly enriched, while generaDialister andPseudobutyrivibrio were significantly depleted in SLE patients. Receiver operating characteristic analysis indicated that the nine genera have the potential to distinguish SLE patients from healthy controls. Conclusions Comparing the dysbiosis of the gut microbiome among SLE patients from China or Spain, may indicate that the gut microbiome profiles of SLE patients are more influenced by disease than ethnicity.